Antibacterial, antifungal and antimycobacterial activities of some substituted thiosemicarbazides and 2,5-disubstituted-1,3,4-thiadiazoles - (:unkn) unknown (My University, 2001)
In this research, some 1-[4-(acetylamino)benzoyl]-4-substituted thiosemicarbazides and 5-[4-(acetylamino)phenyl]-2-substitutedamino-1,3,4-thiadiazoles were screened for antibacterial, antifungal and antimycobacterial activities. The minimum inhibition concentration (MIC) values of compounds have been determined using the microdilution method and the BACTEC 460 radiometric system. Some of the compounds were found to be active against Mycobacterium fortuitum strain and 5-[4-(acetylamino)phenyl]-2-ethylamino-1,3,4-thiadiazole showed a MIC value (16 μg/mL) equivalent to that of tobramycin, which was used as the standard compound.
Keywords: 1-[4-(acetylamino)benzoyl]-4-substituted thiosemicarbazides; 5-[4-(acetylamino) phenyl]-2-substitutedamino-1,3,4-thiadiazoles; Antibacterial; Antifungal and antimycobacterial activities